2014
DOI: 10.1088/1758-5090/7/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic poly (glycerol sebacate)-poly (ϵ-caprolactone) electrospun fibers promote endothelial cell guidance

Abstract: Topographical cell guidance is utilized to engineer highly organized and aligned cellular constructs for numerous tissue engineering applications. Recently, electrospun scaffolds fabricated using poly(glycerol sebacate) (PGS) and poly(ε-caprolactone) (PCL) have shown a great promise to support valvular interstitial cell functions for the development of tissue engineered heart valves. However, one of the major drawbacks of PGS-PCL scaffolds is the lack of control over cellular alignment. In this work we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 65 publications
14
89
4
1
Order By: Relevance
“…To date, biodegradable synthetic thermoset elastomer PGS has been widely explored for various tissue engineering applications [6,8,[20][21][22][23][24][25][26][27][28][29][30]. PGS exhibits faster degradation rate of 17% in 9 weeks in PBS, elastic modulus of around 0.282 MPa, and it's tensile strength is above 0.5…”
Section: Effect Of Polymer Concentrationmentioning
confidence: 99%
“…To date, biodegradable synthetic thermoset elastomer PGS has been widely explored for various tissue engineering applications [6,8,[20][21][22][23][24][25][26][27][28][29][30]. PGS exhibits faster degradation rate of 17% in 9 weeks in PBS, elastic modulus of around 0.282 MPa, and it's tensile strength is above 0.5…”
Section: Effect Of Polymer Concentrationmentioning
confidence: 99%
“…[35,37,38] Comparing to other widely used synthetic polymers such as poly(lactic acid)(PLA) and poly(lactic-co-glycolic acid)(PLGA)-based materials, PGS triggered lower inflammatory responses and minimal fibrous encapsulation. [35][36][37] As a consequence, PGS-based scaffolds are explored for various soft tissue engineering applications, including vascular graft [39][40][41], nerve guide [42], cardiac patch [43], cartilage tissue [44], and retinal transplantation [45]. In addition, it has been reported that PGS supported phenotypes of osteoblasts in vitro and was a promising osteoconductive substrate for bone tissue engineering application.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells cultured on the aligned PGS-PCL fibers exhibited greater proliferation and alignment compared to those cultured on the randomly oriented materials. In addition, alignment of the fibers enabled the endothelial cells to form organized constructs, an important aspect for vascularized tissue structures [12]. …”
Section: Applications Of Responsive and Recognitive Polymers In Regenmentioning
confidence: 99%